Aparecimento de psoríase durante o tratamento das doenças inflamatórias intestinais com infliximabe: A terapia biológica deve ser suspensa? - Denadai, Rafael [UNESP]; Teixeira, Fábio Vieira [UNESP]; Saad-Hossne, Rogério [UNESP] (FapUNIFESP (SciELO), 2012)
Context - Several paradoxical cases of infliximab-induced or-exacerbated psoriatic lesions have been described in the recent years. There is disagreement regarding the need to discontinue infliximab in order to achieve the resolution of these adverse cutaneous reactions specifically in inflammatory bowel disease (IBD) patients. Objective - To systematically review the literature to collect information on IBD patients that showed this adverse cutaneous reaction, focusing mainly on the therapeutic approach. Methods - A systematic literature review was performed utilizing Medline, Embase, SciELO and Lilacs databases. Published studies were identified, reviewed and the data were extracted. Results - Thirty-four studies (69 IBD patients) met inclusion criteria for review. There was inconsistency in reporting of some clinical and therapeutic aspects. Most patients included had Crohn's disease (89.86%), was female (47.83%), had an average age of 27.11 years, and no reported history of psoriasis (84.05%). The patients developed primarily plaque-type psoriasis (40.58%). There was complete remission of psoriatic lesions in 86.96% of IBD patients, existing differences in the therapeutic approaches; cessation of infliximab therapy led to resolution in 47.83% of cases and 43.48% of patients were able to continue infliximab therapy. Conclusion - As increasing numbers of IBD patients with psoriasis induced or exacerbated by infliximab, physicians should be aware of its clinical manifestations so that appropriate diagnosis and treatment are properly established. The decision whether to continue or discontinue infliximab should be individualized.
The onset of psoriasis during the treatment of inflammatory bowel diseases with infliximab: Should biological therapy be suspended?
Keywords: Biological therapy; Inflammatory bowel disease; Infliximab; Psoriasis; adalimumab; alpha interferon; azathioprine; certolizumab pegol; corticosteroid; cyclosporin; etanercept; infliximab; mercaptopurine; mesalazine; methotrexate; mycophenolic acid 2 morpholinoethyl ester; tumor necrosis factor alpha; vitamin D derivative; acanthosis; bibliographic database; corticosteroid therapy; Crohn disease; cytokine production; disease exacerbation; Embase; enteritis; epithelium hyperplasia; histopathology; human; hyperkeratosis; Medline; parakeratosis; phototherapy; physician; plasmacytoid dendritic cell; psoriasis; psoriasis vulgaris; remission; review; skin biopsy; spondylarthritis; systematic review; ulcerative colitis; Antibodies, Monoclonal; Female; Gastrointestinal Agents; Humans; Inflammatory Bowel Diseases; Male